Evaluation Of Health Service Quality From Patients’ Perception - Alsaeed, Saad Youssef Mubarak; Boali, Abdulrahim Abdulhameed Muhsen Al; Alshahi, Mana Saleh; Ozayr, Hassan Ibrahim; Alotaibi, Majed Talq; Alwuhayed, Mohammad Soliman; Almohaisen, Fahad Abdulmohsin; Alshahri, Mohammed Awadh Dif Allah; Khardali, Ali Hamad Hussain; aqial, Salem Hamad Al; zbali, Bassam Khalaf Al (Migration Letters, 2023)
Background: Patient satisfaction is considered one of the preferred outcomes in health care as it is directly related to the reuse of health services and the success of the health care facility. Measuring patients’ perception from health service quality as an important element in the assessment of service quality has attracted much attention in recent years. This study aims to find out how the patients evaluated service quality of clinics. Methods: A cross-sectional study was conducted in outpatient departments (clinics) in hospitals in Jeddah, KSA from January to May 2023. Study sample, 400 patients were randomly selected from four hospitals. Data were collected using a questionnaire, the validity and reliability of which were confirmed in previous study. In order to analyze the data, T-test, ANOVA, and Pearson correlation coefficient were calculated using SPSS 28. Results: indicated that among eight dimensions of health service quality, the patients were more satisfied with physician consultation, services costs and admission process. The highest and lowest mean scores were related to physician consultation (Mean = 4.17), and waiting time (Mean = 2.64), in that order. The total mean score of service quality was 3.73 (± 0.51) out of 5. Outpatient services were assessed as good, moderate and weak by 57.5, 40 and 2.5% of the patients, respectively. There was a significant relationship between th[1]e positive perception of service quality and reason for admission, source of recommendation, gender, education level, health status, and waiting time in the clinics (p < 0.05). Conclusion: The majority of the patients had a positive experience with visiting clinics and perceived service provision as good. In fact, patients’ perceptions of physician consultation, provision of information to patients and the environment of delivering services, are the most important determinants of service quality in clinics.